IMPLEMENTASI GERAKAN KEPEDULIAN SOSIAL MELALUI EKSTRAKURIKULER PRAMUKA DALAM MENUMBUHKAN KARAKTER TA’AWUN PADA PESERTA DIDIK DI MAN 4 KARAWANG - Sri Rahmayu, Rika; Ajat Rukajat; Yadi Fahmi Arifudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of a social awareness movement through Scout extracurricular activities in cultivating ta'awun character among students at MAN 4 Karawang. The study used a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving the principal, Scout leaders, students, and the surrounding community. Data were analyzed through data reduction, data display, and conclusion drawing, while data validity was strengthened through source and method triangulation. The findings show that the social awareness movement was implemented through community service, cleaning activities, homecoming post assistance, assistance for Hajj pilgrims, support for the surrounding community, and helping peers in difficulty. The implementation was carried out through habituation, role modeling, guidance, and direct field practice. Supporting factors included the role of Scout leaders, school support, student participation, and positive community response. Inhibiting factors included low participation among some students, limited time, fatigue after school hours, lack of self-confidence, and parental permission constraints. The implementation contributed to the development of ta'awun character through the affective stages of receiving, responding, valuing, organizing, and characterization. Students showed increased social concern, cooperation, responsibility, and willingness to help others spontaneously in school and community life.